Molecular approaches and challenges for monitoring marine harmful algal blooms in a changing world - Smith, Kirsty F.; Stuart, Jacqui; Rhodes, Lesley L. (Frontiers in Protistology, 2024)
Harmful algal blooms (HABs) of marine microalgae are a growing concern globally and many studies predict that their occurrence, range, and toxicity may increase with climate change, highlighting the need for responsive and adaptable monitoring techniques. Monitoring programmes for HABs require appropriate sampling techniques, accurate and quantitative identification of potentially toxic taxa, and the ability to respond to novel species or HAB events. These challenges have made it difficult to move past traditional techniques, but research tools are continuing to be developed to bring new opportunities for both monitoring programmes and fundamental understanding of these globally significant organisms within a changing landscape.